Response of the Mediterranean Sea Surface Circulation at Various Global Warming Levels: A Multi‐Model Approach - I. M. Parras‐Berrocal; R. Waldman; F. Sevault; S. Somot; N. Gonzalez; B. Ahrens; A. Anav; V. Djurdjević; S. Gualdi; M. E. Hamouda; L. Li; P. Lionello; et al. (Geophysical Research Letters, 2024)
Abstract Changes in Mediterranean circulation patterns due to global warming may have strong socio‐economic and environmental impacts. We analyze the future evolution of the Mediterranean surface circulation under different levels of global warming by using 28 multi‐decadal simulations from a set of fully coupled and high‐resolution regional climate models of the Med‐CORDEX multi‐model initiative. There is no model agreement for a significant basin‐scale modification of the surface circulation. However significant and robust local circulation changes are identified. In particular, the circulation is expected to shift from cyclonic to predominantly anticyclonic in the northern Balearic, while a strengthening of the cyclonic circulation is expected in the southern Adriatic. Furthermore, our results show an increase in the Mediterranean circulation variability primarily associated with a general increase of meso‐scale activity. Generally, we find a linear increase of the identified changes with global warming levels.